The occurrence of Rutstroemia coracina on Quercus ilex leaves in Spain - Galan, Ricardo; Prieto-Garcia, Francisco; Gonzalez, Angeles; Enrique Hermosilla, Carlos (MYCOTAXON, 2013)
The authors report new findings of an apparently rare fungus,Rutstroemia coracina (Rutstroemiaceae). The species grew on old fallen leaves of Quercus ilex subsp. ballota at different localities in Guadalajara and Madrid provinces ( center of Spain) where it was first collected in 1983 and subsequent years. The apothecia are described and illustrated in detail. Microscopic studies, including microtome sections, show a clear gel layer in the ectal excipulum, which allows assignment in the genus Rutstroemia. Since the type material deposited in PC is so scanty and deteriorated that any future revision will be impossible, an epitype is selected here.
The following values have no corresponding Zotero field: pub-location: PO BOX 264, ITHACA, NY 14851-0264 USA publisher: MYCOTAXON LTD
Keywords: Ascomycota; Helotiales; foliicolous fungi; taxonom